2013
DOI: 10.1111/jocn.12067
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of nurses' decisions to activate rapid response teams

Abstract: Nurses can build upon knowledge of facilitators and barriers related to RRT characteristics and nursing unit culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
229
3
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(241 citation statements)
references
References 28 publications
1
229
3
8
Order By: Relevance
“…This would result in MET calls in almost one out of five admitted patients. Moreover, research has shown that ward physicians prefer to be called first and nurses prefer to call the responsible ward physician, before calling the MET [9,33,41,43,44] , thereby involving ward physicians in the treatment of the patient at risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would result in MET calls in almost one out of five admitted patients. Moreover, research has shown that ward physicians prefer to be called first and nurses prefer to call the responsible ward physician, before calling the MET [9,33,41,43,44] , thereby involving ward physicians in the treatment of the patient at risk.…”
Section: Discussionmentioning
confidence: 99%
“…This implicates that training programs concerning critically ill patients should be team oriented and integrated in a broader safety intervention program [49] . In addition, support by management facilitates activation of rapid response teams [43] .…”
Section: Key Elements For Improvementmentioning
confidence: 99%
“…(26) In this context, the professionals' lack of training can generate fear in activations, as they feel embarrassed to show little knowledge of the critical situation and consider themselves unable to handoff the case of the patient to efferent teams. (27) Institutional culture, therefore, can adversely influence professionals towards not executing activations in the correct time and consequently causing delays and worse outcomes. (27) This finding was also observed in the study of Tirkkonen et al 2013, in which even with the identification …”
Section: Discussionmentioning
confidence: 99%
“…(27) Institutional culture, therefore, can adversely influence professionals towards not executing activations in the correct time and consequently causing delays and worse outcomes. (27) This finding was also observed in the study of Tirkkonen et al 2013, in which even with the identification …”
Section: Discussionmentioning
confidence: 99%
“…Conflicting conclusions exist related to activation barriers such as the impact of team support and attitude, impact on workload and human resources, hierarchy of activation, informal social rules, and influence of experience on activation. 19,[31][32][33][34][35][36] Although most studies have been conducted in academic medical centers, a small number of studies have taken place in community hospitals. The population most often studied is nurses working in a medical-surgical setting.…”
mentioning
confidence: 99%